Partition and stability of resveratrol in whey protein isolate oil-in-water emulsion: Impact of protein and calcium concentrations. (October 2017) - Fan, Qi; Wang, Lei; Song, Yuanda; Fang, Zheng; Subirade, Muriel; Liang, Li
Abstract: Whey protein isolate (WPI) is often used in food emulsions and can also interact with resveratrol, a natural amphiphilic polyphenol, this interaction being improved by heat-denaturation. In this study, oil-in-water emulsions stabilised by heat-denatured WPI in the absence and presence of CaCl2 were characterised in terms of size, ζ-potential and protein partition. Partition and stability of resveratrol were also studied as a function of WPI and calcium concentrations. Size of WPI emulsions was dependent on the protein content at the oil–water interface. Partition of resveratrol and WPI was positively proportional at the oil–water interface and in the continuous phase. The stability of resveratrol increased as the concentration of WPI increased, but decreased when the concentration of calcium exceeded 0.20 mm . These data should be useful for simultaneous encapsulation of hydrophobic and amphiphilic bioactive components in a single emulsion and the protection of the inner oil by combination of antioxidant addition.